Effect of color on the odor, flavor, and acceptance properties of foods and beverages - Mahony, Amy (Kansas State University, 2011)
A significant increase in the number of products carried in supermarkets has lead manufacturers to use food color as a way to differentiate their products from competitor’s products or as a form of communication. This report’s overall objective was to review the impact of color on sensory properties of foods and beverages and help product developers understand the multiple sensory properties within a food or beverage that may potentially change by manipulating color. The effect of color on flavor or odor identification, basic taste perception, flavor or odor intensity, quality and refreshment, and consumer acceptance has been extensively researched. Research to date has shown inconsistent findings, although key themes are consistent. Some colors are more appropriate for certain foods and beverages, and product color can be directly linked to palatability. Color cues can be used for flavor identification within a food or beverage, and the presence of certain colors evoke flavor associations within a product. Perceived intensities of basic taste or flavor attributes have increased or decreased merely with color addition. Consumers use color cues to determine quality, therefore color can ultimately affect product acceptance.
Keywords: color; flavor; odor; consumer acceptance; foods; beverages; Food Science (0359)